2003
DOI: 10.1074/jbc.m308424200
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan 3 Intramembrane Proteolysis Is Presenilin/γ-Secretase-dependent and Modulates Cytosolic Signaling

Abstract: The syndecans play critical roles in several signal transduction pathways. The core proteins of these heparan sulfate proteoglycans are characterized by highly conserved transmembrane and intracellular domains which are required for signaling across the membrane and for interaction with cytosolic proteins. However, regulatory mechanisms controlling these functions remain largely unknown. Here we show that, upon ligandinduced primary proteolytic cleavage within the ectodomain, the intracellular domain of syndec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 55 publications
(83 reference statements)
2
73
0
Order By: Relevance
“…So far, all type I transmembrane receptors that are subject to PS1-dependent ␥-secretase cleavage, require a first step of ectodomain shedding (17,18,70,71). Moreover, this first cleavage event appears to be highly regulated, supporting the overall view that the generation of CTFs is likely to be the major regulatory step in the generation of soluble ICDs.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…So far, all type I transmembrane receptors that are subject to PS1-dependent ␥-secretase cleavage, require a first step of ectodomain shedding (17,18,70,71). Moreover, this first cleavage event appears to be highly regulated, supporting the overall view that the generation of CTFs is likely to be the major regulatory step in the generation of soluble ICDs.…”
Section: Discussionmentioning
confidence: 87%
“…The regulation of p75 signaling becomes even more complicated with the finding that p75 is subject to a dual processing starting with shedding of the ectodomain and followed by ␥-secretase cleavage. This adds p75 to the growing list of substrates for regulated intramembrane proteolysis (RIP) that includes the amyloid precursor protein (APP), Notch, Syndecan 3, ErbB4, and N-cadherins among others (13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Shedding of p75 can be induced by protein kinase C (PKC) activators such as the phorbol ester 12-myristate 13-acetate (PMA), reminiscent of the regulatory component of APP shedding by the ADAM (a metalloprotease and disintegrin) family of metalloproteases (23,24).…”
mentioning
confidence: 99%
“…To demonstrate that Alc secretes an A␤-like peptide by the secondary cleavage of CTF1 by ␥-secretase, we designed the Alc␣⌬E construct, which lacks the sequence between Pro 40 and Met 815 in FLAG-Alc␣1 and mimics CTF1 (Fig. 2A).…”
Section: Secretion Of A␤-like Peptide and Release Of The Intracellulamentioning
confidence: 99%
“…Supporting this, we demonstrated here that Alc is a novel substrate of ␥-secretase. Recent publications have reported that a number of membrane proteins can act as ␥-secretase substrates (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Thus, it is now clear that there are a variety of ␥-secretase substrates and that ␥-secretase is not specific for APP and Notch (42).…”
Section: Stabilization and Localization Of Alcicd By Interacting Withmentioning
confidence: 99%
“…More recently, this mechanism of secretase proteolysis has been extended to a second tyrosine kinase, the CSF-1 receptor (23) and several adhesion receptors, including CD44 (24), several cadherins (25)(26)(27), nectin-1␣ (28), syndecan 3 (29), and Deleted in Colorectal Cancer (30). In many of these systems, the secretase-liberated ICD fragment is found in the nucleus and is associated with transcriptional activity.…”
mentioning
confidence: 99%